Ilusi Perencanaan : Analisis Ketidakseimbangan Antara Potensi Ekonomi dan Kapabilitas Pengelolaan BUMDes Ajung - Dea Novica Putri; M. Avan Dwi Adi Nur Kholiq; Ahmad Mush`ab Ridlo Arjuan; Saidatus Sholeha; Ainnur Iqtaara Meilani; Prillinaya Yudhistira; Oryza Ardhiarisca (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to explore the potential of Ajung Village, Kalisat District, Jember Regency, through an analysis of the management planning of a Village-Owned Enterprise (BUMDes) as an instrument of development and community empowerment. Although Ajung Village has significant economic potential, particularly in the agricultural sector, micro-enterprises, and other local economic activities, BUMDes management is still not optimal. This is evident in the lack of a directed business plan, weak coordination between administrators, and minimal evaluation of the business units being run. This study also assesses the role of the village government in supporting BUMDes development and the extent to which community participation can drive the effectiveness of existing programs. Using qualitative descriptive methods through interviews with the village government, BUMDes administrators, and the community, the results show that although community participation is relatively high, the managerial capacity of the administrators remains a major challenge. Lack of training, understanding of financial governance, and the lack of potential mapping have prevented the village BUMDes from functioning optimally as a driver of the village economy. Therefore, this study designs strategies to increase the effectiveness of BUMDes by strengthening the capacity of administrators, optimizing local potential, and synergizing the village government with the community.